A STUDY ON THE GRAVIMETRIC COMPOSITION OF THE SOLID WASTE FROM THE IFRJ CAMPUS DUQUE DE CAXIAS, RJ - Thode Filho, Sérgio; Marques, Aline de Jesus; Santos, Joyce; Ribeiro, Karen Ferraz; Medeiros, Monica Raquel Amaral Moreira de; Santos, Patryck Gonçalves; França, Suelen de Santana (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
It is estimated that every day in Brazil are produced 129,000 tons of garbage. 40% are recyclable material; however, only 2% are recycled. According to the National Policy on Solid Waste, solid waste consists of all waste generated in the limits of the municipality, for households, private companies, public facilities, etc. The law stipulates that, until August 2012, all municipalities of the country must submit a plan for managing solid waste by placing it in operation until 2014. It also establishes a shared responsibility between government, industry, trade and end user management, and solid waste management. The objective of this work was to establish the gravimetric composition of solid waste at the Federal Institute of Rio de Janeiro Campus Duque de Caxias. The gravimetric composition of solid waste expresses the percentage of each component present in these wastes relative to the total weight of the sample. As a result of this work, the plastic is the predominant material in waste composition with 36,04%. The organic material is the second with 28,36% of the total composition. The third position is occupied by paper wastes with 27,40%. The fourth position with 5,43% consists of wastes of tree pruning, sweeping waste, and tile floors, etc. In the fifth position, the metals represent 2,20% of the total composition. Basically, the metallic waste is composed of aluminum cans. In last position with 0,57% are the waste glass. This study identified the composition of the waste, the volume of discarded material, set the correct techniques for handling and storage, as well as studying a correct final destination for each.